Loan interest rates, credit guarantees, and lifestyle on credit making decisions at financing companies - Hendri Herman; Vargo Christian L Tobing; Andi Hidayatul Fadlilah; Syahrial Shaddiq; Muhammad Bahit (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
Loan interest rates play a pivotal role in the borrowing and lending process. They impact the affordability of loans for borrowers, the profitability and risk management for lenders, and are influenced by economic conditions and regulations. Before taking out any loan, it's important to carefully consider the interest rate and its implications for financial situation.This research aims to look at the effect of credit interest rates and credit guarantees on credit-making decisions on financing companies in Batam. This research is a quantitative descriptive study with the distribution of questionnaires to respondents who apply for credit at finance companies at random with a total of 96 responden. From the results of the study, it was obtained that credit rates have a significant effect on credit decision-making, credit guarantees have a significant effect on credit decisions, lifestyle has an insignificant effect on credit-making decisions,and credit interest rates, credit guarantees. and lifestyle simultaneously have a significant effect on credit-making decisions. This research is expected to contribute to the community to be more thorough about the advantages and disadvantages of buying goods on credit. The conclusion is that interest rates and credit guarantees significantly influence credit, and business actors can take even better policies related to interest rates and credit guarantees.